HaploSNP affinities and linkage map positions illuminate subgenome composition in the octoploid, cultivated strawberry (Fragaria × ananassa). (January 2016) - Sargent, D.J.; Yang, Y.; Šurbanovski, N.; Bianco, L.; Buti, M.; Velasco, R.; Giongo, L.; Davis, T.M.
Highlights: The IStraw90 ® array was evaluated as a generic tool for linkage map development. A map with more than 8, 000 markers spanning 28 linkage groups was constructed. Analysis of haploSNP markers identified F. vesca and F. iinumae sub-genomes A new model of subgenome composition and evolution was proposed Abstract: The cultivated strawberry, Fragaria × ananassa possesses a genetically complex allo-octoploid genome. Advances in genomics research in Fragaria, including the release of a genome sequence for F. vesca, have permitted the development of a high throughput whole genome genotyping array for strawberry, which promises to facilitate genetics and genomics research. In this investigation, we used the Axiom ® IStraw90 ® array for linkage map development, and produced a linkage map containing 8, 407 SNP markers spanning 1, 820 cM. Whilst the linkage map provides good coverage of the genome of both parental genotypes, the map of 'Monterey' contained significantly fewer mapped markers than did that of 'Darselect'. The array contains a novel marker class known as haploSNPs, which exploit homoeologous sequence variants as probe destabilization sites to effectively reduce marker ploidy. We examined these sites as potential indicators of subgenomic identities by using comparisons to allele states in two ancestral diploids. On this basis, haploSNP loci could be inferred to be derived from F. vesca, F. iinumae, or from an unknown source. When the identity classifications of haploSNPs were considered in conjunction with their respective linkage map positions, it was possible to define two discrete subgenomes, while the remaining homoeologues of each chromosome could not be partitioned into two discrete subgenomic groupings. These findings suggested a novel hypothesis regarding octoploid strawberry subgenome structure and evolutionary origins.